2021
DOI: 10.1111/ejn.15217
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal mu opioid receptors are modulated following cocaine self‐administration in rat

Abstract: Addiction is a multifactorial disease involving genetic, psychological, and environmental factors, which has detrimental consequences for individuals and society. It is characterized by excessive intake over time, craving, continued drug use despite negative consequences and relapse (Koob & Volkow, 2016). The progression of addiction is associated with neuroplastic changes (Robinson & Kolb, 1999;Ron & Jurd, 2005), whereby altered gene expression impacts neuronal function and behavior (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The blockade of κ opioid receptors selectively attenuated increased cocaine self-administration in rats with extended access to cocaine [ 66 ]. In addition, it has recently been demonstrated that, following self-administration in rats, cocaine modulates hippocampal mu opioid receptors [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The blockade of κ opioid receptors selectively attenuated increased cocaine self-administration in rats with extended access to cocaine [ 66 ]. In addition, it has recently been demonstrated that, following self-administration in rats, cocaine modulates hippocampal mu opioid receptors [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they found that conditional overexpression of MORs in DG neural stem cells led to enhanced morphine self‐administration, confirming the role of DG MORs in the establishment of morphine addiction. 269 Furthermore, another two studies reported that cocaine addiction increased the MORs expression and functionality in the rat hippocampus, 270 and adolescent morphine exposure enhanced the MORs‐mediated G‐protein activity in the hippocampus and morphine preference in the conditioned place preference test in adult mice. 271 These two studies provide us with a glimpse of hippocampal MORs alteration under drug addiction situations.…”
Section: Reward Circuitry Addiction and Morsmentioning
confidence: 99%
“…Samples (n=5-7/group) were prepared as previously described [51] with minor modifications. Briefly, frozen tissues were ground on carbonic ice before fixation (1% formaldehyde) and quenched with glycine (0.125M).…”
Section: Epigenetic Analysis 251 Chromatin Immunoprecipitationmentioning
confidence: 99%
“…Samples were washed and reverse cross-linking was performed at 65°C overnight, and DNA purified (DNA mini elute kit, Qiagen, France). Additionally, a negative control without IgG was performed to test for nonspecific binding [51]. The % of enrichment was calculated as follow: (signal H3K27acsignal no ab)/Input *100.…”
Section: Epigenetic Analysis 251 Chromatin Immunoprecipitationmentioning
confidence: 99%